Pharmacy : an introduction to the profession - Posey, L. Michael; Kahaleh, Abir A.; American Pharmacists Association; American Pharmacists Association (Washington, DC : American Pharmacists Association, 2016)
In this updated third edition, the author give readers an insider's perspective on the workings of the pharmacy profession. They discuss key topics such as government regulation, career pathways, membership organizations, communication skills, and ethics. In addition, they address how patient care services are changing the practice of pharmacy.
Pharmacy's cadence : drumbeat of a profession / L. Michael Posey and Abir A. (Abby) Kahaleh -- Development of pharmacy in history as a healing profession / L. Michael Posey -- Pharmacy reborn : from clinical services to pharmacists' patient care services / Abir A. (Abby) Kahaleh -- Communications in pharmacy practice / Bruce A. Berger -- Ethics in pharmacy practice -- Career planning : contemporary pharmacy practice areas / Abir A. (Abby) Kahaleh -- Governmental and voluntary oversight of pharmacy / L. Michael Posey -- Pharmacy associations : opportunities for pharmacists and student pharmacists / Abir A. (Abby) Kahaleh -- Using the pharmacy literature and writing for it / L. Michael Posey -- Postgraduate educational and training opportunities / Abir A. (Abby).
Title from title screen (viewed March 15, 2017).
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
WorldCat record variable field(s) change: 650
Keywords: Pharmacy; Pharmaceutical services; Vocational guidance; Pharmacy; Pharmaceutical Services; Career Choice; Education, Pharmacy; Vocational Guidance; pharmacies (health facilities ); vocational guidance; Pharmacy; Electronic books